Liquidity and Leverage of Cryptocurrency in Financial Risk Management of Indodax Exchange - Daming, Sudirman; Widyawati, Widyawati (Pascasarjana STIE Amkop Makassar, 2024)
Cryptocurrency trading presents unique financial risks, particularly concerning liquidity and leverage, which significantly impact exchange stability and investor decision-making. This study analyzes the role of liquidity and leverage in the financial risk management strategies of Indodax, Indonesia's largest cryptocurrency exchange. Liquidity is a crucial factor affecting price stability and market efficiency, while leverage amplifies both potential gains and losses, increasing exposure to volatility. Using a quantitative approach, this research evaluates the correlation between liquidity, leverage, and risk management practices at Indodax. The findings indicate that higher liquidity reduces price manipulation risks and enhances market efficiency, whereas excessive leverage increases vulnerability to liquidation and systemic risks. The study highlights the importance of robust risk management strategies, including margin policies and liquidity reserves, to ensure market stability. These insights contribute to a better understanding of financial risk mitigation in cryptocurrency exchanges and provide recommendations for improving regulatory frameworks and investor protections. Keywords: Liquidity, Leverage, Cryptocurrency, Financial Risk Management, Indodax Exchange